Prostaglandin Reductase 1 as a Potential Therapeutic Target for Cancer Therapy - Wang, Xing; Yin, Guobing; Zhang, Wei; Song, Kunling; Zhang, Longbin; Guo, Zufeng (Frontiers in Pharmacology, 2021)
Altered tumor metabolism is a hallmark of cancer and targeting tumor metabolism has been considered as an attractive strategy for cancer therapy. Prostaglandin Reductase 1 (PTGR1) is a rate-limiting enzyme involved in the arachidonic acid metabolism pathway and mainly responsible for the deactivation of some eicosanoids, including prostaglandins and leukotriene B4. A growing evidence suggested that PTGR1 plays a significant role in cancer and has emerged as a novel target for cancer therapeutics. In this review, we summarize the progress made in recent years toward the understanding of PTGR1 function and structure, highlight the roles of PTGR1 in cancer, and describe potential inhibitors of PTGR1. Finally, we provide some thoughts on future directions that might facilitate the PTGR1 research and therapeutics development.